Variation over time in medical conditions and health service utilization of children with down syndrome - Thomas, K.; Bourke, J.; Girdler, Sonya; Bebbington, A.; Jacoby, P.; Leonard, H. (Mosby, Inc., 2011)
Objectives: To compare the prevalence of parent reported medical conditions and rates of health service utilization in school-aged children with Down syndrome in Western Australia in 1997 and 2004. Study design: We compared two cross-sectional surveys completed by parents of children with Down syndrome identified from population-based sources in 1997 (n = 210) and 2004 (n = 208). Surveys collected information on family demographics, medical conditions, health issues, and service utilization. The analysis described medical conditions in 2004 and compared frequencies in both years. Regression analyses compared medical conditions and health utilisation in the two cohorts. Results: In 2004, children with Down syndrome had greater odds of having a bowel condition (OR, 1.69; 95%, 1.16 to 2.45; P = .01), were less likely to have a current problem due to their cardiac condition (OR, 0.32; 95% CI, 0.15 to 0.68, P = .003), and demonstrated an overall reduction in episodic illnesses and infections. The use of GP services (incidence rate ratio [IRR] = 0.91; 95% CI, 0.83 to 1.00, P = .05) and combined medical specialist visits (IRR = 0.92; 95% CI, 0.84 to 1.01; P = .09) were reduced in 2004, as were overnight hospital admissions (IRR = 0.60; 95% CI, 0.37 to 0.96; P = .03) and length of stay (IRR = 0.33; 95% CI, 0.24 to 0.44; P < .001). Conclusions: The health status of children with Down syndrome has varied over time with reductions in current cardiac problems, episodic illnesses, and health service use. Research is now needed to investigate the impact of these changes on the overall health and quality of life of children and families living with Down syndrome. Copyright © 2011 Mosby Inc. All rights reserved.